AN ANALYSIS OF CODE MIXING USED IN DEDDY CORBUZIER VIDEO PODCAST - qori indah putri nasution (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The purposes of this research are to find out: 1) the types of code mixing used in Deddy Corbuzier video podcast on youtube channel and 2) the factors why Deddy Cobuzier used code mixing in video podcast on youtube channel. Documentation used in collecting the data and triangulation used in checking trustworthiness the data. The result of the research showed the types of code mixing used in Deddy Corbuzier video podcast on youtube channel is adopted from Hofman includes 96% Intra-sentential, 2.2 % Intra-lexical, and 2.2% Involving a change of pronunciation. Furthermore, the factors why Deddy Corbuzier used code mixing in video podcast on youtube channel because particular topic, interjection, and repetition for clarifying Keywords: Code Mixing,Deddy Corbuzier,Video Podcast, Youtube Channel. Abstrak: Tujuan dari penelitian ini untuk mengetahui: 1) tipe pencampuran kode yang digunakan dalam podcast video Deddy Corbuzier di saluran youtube dan 2) faktor-faktor mengapa Deddy Cobuzier menggunakan pencampuran kode dalam podcast video di saluran youtube. Dokumentasi digunakan dalam mengumpulkan data dan triangulasi digunakan untuk memeriksa keabsahan data. Hasil penelitian menunjukkan tipecampur kode yang digunakan dalam video podcast Deddy Corbuzier pada saluran youtube yang diadopsi dari Hofman meliputi 96% Intra-sentential, 2.2% Intra-lexical, dan 2.2% yang melibatkan perubahan pengucapan. Selanjutnya faktor-faktor mengapa Deddy Cobuzier menggunakan campur kode dalam video podcast di saluran youtube karena adanya partikular topik, interjeksi, dan pengulangan untuk klarifikasi. Kata Kunci: campur kode, Deddy Corbuzier, podcast video ,saluran youtube.